Implementasi Metode Pembelajaran Sorogan Dan Bandongan Dalam Pengajaran Mata Pelajaran Pendidikan Agama Islam Di Sd Nu Banat Banin Lamongan - Ulil Albab; M. Ulul Albab; Novitasari Novitasari; Ja’far Shodiq; Adinda Talia Salsabilah (Universitas Islam Lamongan, 2022)
Sorogan and Bandongan learning methods that characterize learning methods in Islamic boarding schools are applied in formal institutions, especially at the Elementary School level. SD NU Banat Banin Lamongan has implemented the boarding school learning system in teaching and learning activities on Islamic Education subjects in the classroom. The results showed that the background of the implementation of the Sorogan and Bandongan learning methods in teaching of Islamic Religious Education subjects at SD NU Banat Banin Lamongan was to put more emphasis on student understanding, in addition, the application of the Sorogan and Bandongan learning methods was also very simple, so that all children students are expected to be able to understand the material quickly. In the process of implementation, it is carried out in three stages. The first is the preparation stage. The teacher always checks the readiness of his students. The second is the implementation phase. For the Sorogan method, students who get their turn to read, are told to go forward and sit facing the teacher, then read the reading text prepared in the last week. For the Bandongan method, the teacher reads and translates the reading text contained in the textbook. And the third stage is the closing stage. The teacher will give an explanation of the material that has been read and translated. Based on the results of the research, in implementing the Sorogan and Bandongan learning methods, it should be improved and improved in all activities and learning.